2014
DOI: 10.1016/j.virol.2014.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 limits human influenza A virus (H1N1) propagation in mouse embryo-derived fibroblasts

Abstract: Caveolin expression supports the multiplication of retro-, ortho- and paramyxoviruses in susceptible cells. However, human influenza A virus (IAV), an orthomyxovirus, does not multiply efficiently in mouse embryo fibroblasts (MEFs), which are abundant in caveolin-1 (Cav-1). Surprisingly, the absence of Cav-1 in a MEF cell line removed the block for IAV replication and raised the infectious titer 250-fold, whereas the re-introduction of Cav-1 reversed the effect. The monitoring of cellular pathways revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…For example, overexpression of CAV-1 significantly decreases the transcription level of HIV-1, and the decrease of CAV-1 expression leads to an enhancement of HIV-1 replication. As well known, HIV actually benefits from the activation of host inflammatory responses [104,105]. Further investigations suggested that CAV-1 suppresses the NF-κB p65 acetylation, a requirement for signaling activation [106,107].…”
Section: The Role Of Caveolae/cav-1 In Virus Replicationmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, overexpression of CAV-1 significantly decreases the transcription level of HIV-1, and the decrease of CAV-1 expression leads to an enhancement of HIV-1 replication. As well known, HIV actually benefits from the activation of host inflammatory responses [104,105]. Further investigations suggested that CAV-1 suppresses the NF-κB p65 acetylation, a requirement for signaling activation [106,107].…”
Section: The Role Of Caveolae/cav-1 In Virus Replicationmentioning
confidence: 90%
“…Strikingly, the elevated levels of ROS and apoptosis cause the increase of IVA virion yield. In other words, CAV-1 plays a role in limiting IVA infection [105].…”
Section: The Role Of Caveolae/cav-1 In Other Viruses Infection-related Signal Transductionmentioning
confidence: 99%
“…Although the combined data suggest a function of caveolae in viral biogenesis, an association with caveolin-1 alone does not directly demonstrate the involvement of caveolae in virus morphogenesis. In addition, siRNA-mediated knockdown of caveolin-1 was shown to have no effect on RSV morphogenesis and infection in cultured cells (Kipper et al, 2015), and there is some evidence that caveolin-1 might have an anti-viral role during virus infection (Gabor et al, 2013; Bohm et al, 2014; He et al, 2016). Thus, the role of caveolin-1 and caveolae in virus-infected cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, both RAB7A and CD63 are required for the HIV-1 replication cycle 25 26 . In addition, LSD1, HSPA5, and CAV-1 have been reported to influence the efficiency of viral infection and replication 27 28 29 30 31 ; NPC1 is the key influencer for Ebola virus to enter cells 32 ; SEC22b can inhibit the release of infectious viral progeny 33 ; and the down-regulation of CD59 is associated with the development of hepatitis B cytotoxicity 34 .…”
Section: Resultsmentioning
confidence: 99%